EFFECT OF BALANCE TRAINING EXERCISES ON KICKBOXING ATHLETE‘S BALANCE, MUSCLE STRENGTH AND REACTION TIME IN CHRONIC ANKLE JOINT INSTABILITY: A CASE STUDY - Gedrimas, Dovydas; Lideikaitė, Martyna (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The purpose of this study was to evaluate the effect of 12 weeks of balance training on balance, muscle strenght and reaction time of an kickboxing athlete with chronic ankle instability. Ankle instability causes long-term pain, disability, negatively affects quality of life and reduces physical activity and time to returning to the sports. The novelty of this study is that there is a lack of research on the effect of balance training exercises on balance, reaction time and strength of the muscles surrounding the ankle joint in kickboxers with chronic ankle instability.